The Effects of Allium sativum Extracts on Biofilm Formation and Activities of Six Pathogenic Bacteria - Mohsenipour, Zeinab (Jundishapur J Microbiol, 2015)
BACKGROUND: Garlic is considered a rich source of many compounds, which shows antimicrobial effects. The ability of microorganisms to adhere to both biotic and abiotic surfaces and to form biofilm is responsible for a number of diseases of chronic nature, demonstrating extremely high resistance to antibiotics. Bacterial biofilms are complex communities of sessile microorganisms, embedded in an extracellular matrix and irreversibly attached to various surfaces. OBJECTIVES: The present study evaluated the antimicrobial activity of Allium sativum extract against the biofilms of six pathogenic bacteria and their free-living forms. The clinical isolates in this study had not been studied in any other studies, especially in regard to biofilm disruption and inhibition of biofilm cell metabolic activity. MATERIALS AND METHODS: Antimicrobial activities of A. sativum L. extracts (methanol and ethanol extracts) against planktonic forms of bacteria were determined using the disc diffusion method. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) values were evaluated by a macrobroth dilution technique. The anti-biofilm effects were assessed by microtiter plate method. RESULTS: The results showed that the A. sativum L. extract discs did not have any zone of inhibition for the tested bacteria. However, The MIC values of A. sativum L. extracts (0.078 - 2.5 mg/mL) confirmed the high ability of these extracts for inhibition of planktonic bacteria. A. sativum L. extracts were efficient to inhibit biofilm structures and the concentration of each extract had a direct relation with the inhibitory effect. CONCLUSIONS: Finally, it can be suggested that the extracts of this plant be applied as antimicrobial agents against these pathogens, particularly in biofilm forms.